Impact of ERCP simulator training on early ERCP learning curves of novice trainees: a cohort study - van der Wiel, Sophia Elisabeth; Rauws, Erik; Van Gool, Stijn; Wang, Dong; Hu, Bing; Kylanpaa, Leena; Webster, George J.M.; James, Martin; Koch, Arjun Dave; Bruno, Marco (Endoscopy International Open, 2023)
Background and study aim Simulator-based training has been extensively studied in training gastroduodenoscopy and colonoscopy and shown to significantly improve learning curves of novices. Data on simulator-based training in endoscopic retrograde cholangiopancreatography (ERCP) are scarce. We aimed to determine the impact of 2-day intensive hands-on simulator training on the course of the learning curve of novice trainees.Methods We conducted a prospective cohort study using a validated mechanical ERCP simulator (Boškoski-Costamagna ERCP Trainer). Six trainees were allocated to the simulation course program (SG). Each of these trainees were paired with an endoscopy trainee starting regular ERCP training at the same center who had no exposure to a simulation course program (control group; CG). The course included lectures, live ERCP demonstrations, and hands-on ERCP training to educate trainees in basic techniques related to cannulation, stent placement, stone extraction and stricture management. After the course, both the SG and CG started formal ERCP training in their respective centers. The Rotterdam Assessment Form for ERCP was used to register each performed ERCP. Simple moving average was applied to create learning curves based on successful common bile duct (CBD) cannulation. Outcomes were plotted against a historical cohort (HC).Results Thirteen trainees were included, six trainees in the SG and seven trainees in the CG, with a total of 717 ERCPs. Mean successful ERCP cannulation rate was higher for the simulator group at baseline compared to both CG and HC, 64% versus 43% and 42%, respectively. Differences became less explicit after 40 ERCPs, but persisted until a median of 75 ERCPs.Conclusions We demonstrate that 2-day hands-on simulator-based ERCP training course has a positive effect on the learning curves of ERCP trainees and should be considered an integral part of the training curricula for ERCP to develop skills prior to patient-based training.
Keywords: Pancreatobiliary (ERCP/PTCD); Pancreatobiliary (ERCP/PTCD); ERC topics; Quality and logistical aspects; Training